Using Gabmap - Therese Leinonen; çağrı çöltekin; John Nerbonne (Elsevier, 2022)
Gabmap is a freely available, open-source web application that analyzes the data of language variation, e.g. varying words for the same concepts, varying pronunciations for the same words, or varying frequencies of syntactic constructions in transcribed conversations. Gabmap is an integrated part of CLARIN (see e.g. http://portal.clarin.nl). This article summarizes Gabmap's basic functionality, adding material on some new features and reporting on the range of uses to which Gabmap has been put. Gabmap is modestly successful, and its popularity underscores the fact that the study of language variation has crossed a watershed concerning the acceptability of automated language analysis. Automated analysis not only improves researchers’ efficiency, it also improves the replicability of their analyses and allows them to focus on inferences to be drawn from analyses and other more abstract aspects of that study.